Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Discover comprehensive solutions to your questions from a wide network of experts on our user-friendly platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
To find the value of [tex]\( k \)[/tex] when [tex]\( f(x+3) = x^2 + kx - 21 \)[/tex], we need to substitute [tex]\( x + 3 \)[/tex] into the given function [tex]\( f(x) = x^2 - 2x - 24 \)[/tex] and then compare the resulting expression to [tex]\( x^2 + kx - 21 \)[/tex].
Let's start with the given function:
[tex]\[ f(x) = x^2 - 2x - 24 \][/tex]
We want to find [tex]\( f(x+3) \)[/tex]:
1. Substitute [tex]\( x + 3 \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(x+3) = (x + 3)^2 - 2(x + 3) - 24 \][/tex]
2. Expand [tex]\( (x + 3)^2 \)[/tex]:
[tex]\[ (x + 3)^2 = x^2 + 6x + 9 \][/tex]
3. Substitute and simplify:
[tex]\[ f(x+3) = x^2 + 6x + 9 - 2(x + 3) - 24 \][/tex]
[tex]\[ = x^2 + 6x + 9 - 2x - 6 - 24 \][/tex]
[tex]\[ = x^2 + 6x - 2x + 9 - 6 - 24 \][/tex]
[tex]\[ = x^2 + 4x + 9 - 6 - 24 \][/tex]
[tex]\[ = x^2 + 4x - 21 \][/tex]
Now, we compare this expression to [tex]\( x^2 + kx - 21 \)[/tex]:
[tex]\[ x^2 + 4x - 21 \][/tex]
It is clear that the coefficient of [tex]\( x \)[/tex] in [tex]\( x^2 + 4x - 21 \)[/tex] is 4. Hence, [tex]\( k = 4 \)[/tex].
Therefore, the value of [tex]\( k \)[/tex] is:
[tex]\[ \boxed{4} \][/tex]
The correct answer is:
D. 4
Let's start with the given function:
[tex]\[ f(x) = x^2 - 2x - 24 \][/tex]
We want to find [tex]\( f(x+3) \)[/tex]:
1. Substitute [tex]\( x + 3 \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(x+3) = (x + 3)^2 - 2(x + 3) - 24 \][/tex]
2. Expand [tex]\( (x + 3)^2 \)[/tex]:
[tex]\[ (x + 3)^2 = x^2 + 6x + 9 \][/tex]
3. Substitute and simplify:
[tex]\[ f(x+3) = x^2 + 6x + 9 - 2(x + 3) - 24 \][/tex]
[tex]\[ = x^2 + 6x + 9 - 2x - 6 - 24 \][/tex]
[tex]\[ = x^2 + 6x - 2x + 9 - 6 - 24 \][/tex]
[tex]\[ = x^2 + 4x + 9 - 6 - 24 \][/tex]
[tex]\[ = x^2 + 4x - 21 \][/tex]
Now, we compare this expression to [tex]\( x^2 + kx - 21 \)[/tex]:
[tex]\[ x^2 + 4x - 21 \][/tex]
It is clear that the coefficient of [tex]\( x \)[/tex] in [tex]\( x^2 + 4x - 21 \)[/tex] is 4. Hence, [tex]\( k = 4 \)[/tex].
Therefore, the value of [tex]\( k \)[/tex] is:
[tex]\[ \boxed{4} \][/tex]
The correct answer is:
D. 4
We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.